Predictors of Chikungunya rheumatism: a prognostic survey ancillary to the TELECHIK cohort study - Gérardin, Patrick (BioMed Central, 2013)
INTRODUCTION: Long-lasting relapsing or lingering rheumatic musculoskeletal pain (RMSP) is the hallmark of Chikungunya virus (CHIKV) rheumatism (CHIK-R). Little is known on their prognostic factors. The aim of this prognostic study was to search the determinants of lingering or relapsing RMSP indicative of CHIK-R. METHODS: Three hundred and forty-six infected adults (age ≥ 15 years) having declared RMSP at disease onset were extracted from the TELECHIK cohort study, Reunion island, and analyzed using a multinomial logistic regression model. We also searched for the predictors of CHIKV-specific IgG titres, assessed at the time of a serosurvey, using multiple linear regression analysis. RESULTS: Of these, 111 (32.1%) reported relapsing RMSP, 150 (43.3%) lingering RMSP, and 85 (24.6%) had fully recovered (reference group) on average two years after acute infection. In the final model controlling for gender, the determinants of relapsing RMSP were the age 45-59 years (adjusted OR: 2.9, 95% CI: 1.0, 8.6) or greater or equal than 60 years (adjusted OR: 10.4, 95% CI: 3.5, 31.1), severe rheumatic involvement (fever, at least six joints plus four other symptoms) at presentation (adjusted OR: 3.6, 95% CI: 1.5, 8.2), and CHIKV-specific IgG titres (adjusted OR: 3.2, 95% CI: 1.8, 5.5, per one unit increase). Prognostic factors for lingering RMSP were age 45-59 years (adjusted OR: 6.4, 95% CI: 1.8, 22.1) or greater or equal than 60 years (adjusted OR: 22.3, 95% CI: 6.3, 78.1), severe initial rheumatic involvement (adjusted OR: 5.5, 95% CI: 2.2, 13.8) and CHIKV-specific IgG titres (adjusted OR: 6.2, 95% CI: 2.8, 13.2, per one unit increase). CHIKV specific IgG titres were positively correlated with age, female gender and the severity of initial rheumatic symptoms. CONCLUSIONS: Our data support the roles of age, severity at presentation and CHIKV specific IgG titres for predicting CHIK-R. By identifying the prognostic value of the humoral immune response of the host, this work also suggest a significant contribution of the adaptive immune response to the physiopathology of CHIK-R and should help to reconsider the paradigm of this chronic infection primarily shifted towards the involvement of the innate immune response.